1935
DOI: 10.1121/1.1915795
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Impedance of Small Orifices

Abstract: Data are presented giving the measured acoustic reactance and resistance for a number of circular orifices varying in diameter from 1 cm down to 0.034 cm, and for a rectangular orifice 1.9 cm×0.075 cm. The measurements were made for various particle velocities, the corresponding Reynolds numbers varying from 0.7 to 3000, roughly. The reactance is found substantially independent of the particle velocity; a formula for computing it is given. The resistance approaches a constant value as the velocity is sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
3

Year Published

1945
1945
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(48 citation statements)
references
References 0 publications
0
44
0
3
Order By: Relevance
“…Early work by Sivian (1935) to examine small-orifice impedance was expanded by Ingard & Labate (1950) who observed that the size of the orifice could significantly change the sound-induced flow inside the orifice due to viscosity, possibly generating an oscillatory turbulent jet, and displaying a nonlinear impedance. Rogers & Hersh (1975) and Hersh & Rogers (1976) used a single orifice mounted within a water tunnel to visualize the oscillatory flow to develop a semi-empirical impedance model that accounted for high-amplitude conditions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Early work by Sivian (1935) to examine small-orifice impedance was expanded by Ingard & Labate (1950) who observed that the size of the orifice could significantly change the sound-induced flow inside the orifice due to viscosity, possibly generating an oscillatory turbulent jet, and displaying a nonlinear impedance. Rogers & Hersh (1975) and Hersh & Rogers (1976) used a single orifice mounted within a water tunnel to visualize the oscillatory flow to develop a semi-empirical impedance model that accounted for high-amplitude conditions.…”
Section: Literature Reviewmentioning
confidence: 98%
“…here is a large number of papers on the effect of high level acoustic excitation on the acoustic properties of perforates and orifice plates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Orifice plates and perforates appear in many technical applications where they are exposed to a combination of high acoustic excitation levels and either grazing or bias flow or a combination.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear effect of high level acoustic excitation has for instance been studied in Ref. [1][2][3][4][5][6][7][8][9][10]. It is well known from this literature that perforates can become non-linear at fairly low acoustic excitation levels.…”
Section: Introductionmentioning
confidence: 99%